2018
DOI: 10.1159/000494542
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Expression Profiles for the Characterization of Different Bladder Cancer Grade

Abstract: Background/Aims: Bladder cancer (BC) is one of the most frequent urologic tumors worldwide. However, long non-coding RNA(lncRNA) expression profiles in BC progression remain unclear. This study aimed to explore lncRNA expression profiles in different grades of bladder cancer and normal urothelium tissues. Methods: We performed high-throughput sequencing in BC tissues of different grade and obtained the expression profiles of its lncRNAs. Then, aberrantly expressed lncRNAs were validated by quantitative reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…LncRNAs regulate gene expression at the post-transcriptional level, including protein synthesis, RNA maturation, and transport (8). Previous studies report that lncRNAs play a role in tumorigenesis and metastasis in different cancer types (3,(9)(10)(11)(12). Several lncRNAs are reported to play important roles in the progression and invasion of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs regulate gene expression at the post-transcriptional level, including protein synthesis, RNA maturation, and transport (8). Previous studies report that lncRNAs play a role in tumorigenesis and metastasis in different cancer types (3,(9)(10)(11)(12). Several lncRNAs are reported to play important roles in the progression and invasion of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the latter our analysis also revealed lncRNAs ( DLX6-AS1 ) that regulate the expression of distant mRNAs ( DLX6-AS1 ) 26,27 . Interestingly, previous brain related studies have also found some of our top DE lncRNAs, LBX2-AS1 28 and LUCAT1 29,30 as significantly co-expressed with other mRNAs expressed in brain (Fig. 1c).…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, LUCAT1 also acts on esophageal squamous cell carcinoma where it regulates the stability of DNMT1 leading to the formation and metastasis of this carcinoma 28 . LUCAT1 and CCNB1 had a positive relationship in regulating the progress of bladder cancer 29 . It was also found to present a differential expression on head and neck squamous cell carcinoma, together with other lncRNAs 30 and it exerts an oncogenic function in cervical cancer by binding to miR-181a 31 .…”
Section: Introductionmentioning
confidence: 92%